An assessment of diversity and current status of bats in Cu Lao Cham-Hoi An biosphere reserve - Thong, Vu Dinh (Academia Journal of Biology, 2016)
Cu Lao Cham-Hoi An Biosphere Reserve, which is commly known as Cu Lao Cham, is a well-known locality in Vietnam. It has received attention from national and international scientists and public communities. However, biodiversity of the biosphere is still poorly studied. In order to provide a confirmed database of bats from Cu Lao Cham, the author conducted two bat surveys with emphases on taxonomy and echolocation between May and August 2015. The survey results indicate that Cu Lao Cham is a home to 7 species belonging to 4 genera, 4 families, 2 suborders: Cynopterus horsfieldii, Rhinolophus affinis, R. pusillus, Hipposideros galeritus, H. grandis, H. pomona và Pipistrellus abramus. Of which, H. grandis is the most common species throughout the reserve. The species was recorded during the whole surveys and at almost all forest habitats. There is not sufficient evidence to confirm the occurrence of the five bat species, which was listed in a previously published literature (Hipposideros armiger, H. bicolor, H. larvatus, Pipistrellus ceylonicus và P. javanucus) in Cu Lao Cham. This paper provides a confirmed data on diversity and conservation status of bats of the reserve.